Providing interprofessional learning experiences for students of health and social care: The SOYAÇ model from Istanbul - Gür, Kamer; Kolaç, Nurcan; Yurt, Seher; Tümerdem Çalık, Burcu; Beyhan, Abdullah; Bademci, Özden (Fenerbahce University, 2024)
The aim of our research was to determine the effectiveness of a six-month, community-based intervention on student interns’ perceptions of interdisciplinary education and interprofessional learning. All participants were registered volunteers attending the We’re at School in Üsküdar internship program coordinated by the Maltepe University Research and Application Center for Children Living and Working on the Street (Turkish acronym SOYAÇ). This model offers students of health and social care an immersive 5 days a week experience over a duration of 6 months, providing cooperative, multidisciplinary applications in a community-based context in Istanbul. A quasi experimental, pre-post approach was used. The sample consists of 43 undergraduate and graduate students studying in the Health and Social Care Departments of two SOYAÇ stakeholder universities. Data collection tools are the Interdisciplinary Education Perception Scale and Interprofessional Learning Scale. We found increases and significant differences in posttest scores for Interprofessional Learning, Competence and Autonomy, Perception of Actual Cooperation, Readiness for Learning, and Professional Identity (p<0.05). Our findings confirm a significant beneficial impact of the SOYAÇ Model on student perceptions of interacting and cooperating with other vocations.

Araştırmamızın amacı, stajyer öğrencilerin disiplinlerarası eğitim ve meslekler arası öğrenmeye ilişkin algıları üzerinde altı aylık toplum temelli bir müdahalenin etkinliğini belirlemekti. Katılımcıların tamamı Maltepe Üniversitesi Sokakta Yaşayan ve Çalışan Çocuklar Araştırma ve Uygulama Merkezi (Türkçe kısaltması SOYAÇ) tarafından koordine edilen Üsküdar'da Okuldayız staj programına katılan kayıtlı gönüllülerden oluştu. Bu model, sağlık ve sosyal bakım öğrencilerine 6 ay boyunca haftanın 5 günü sürükleyici bir deneyim sunarak İstanbul'da toplum temelli bir bağlamda işbirlikçi, çok disiplinli uygulamalar sağlar. Yarı deneysel, ön-sonraki bir yaklaşım kullanıldı. Örneklemi SOYAÇ'ın paydaş iki üniversitesinin Sağlık ve Sosyal Hizmetler Bölümlerinde öğrenim gören 43 lisans ve yüksek lisans öğrencisi oluşturmaktadır. Veri toplama araçları Disiplinlerarası Eğitim Algı Ölçeği ve Mesleklerarası Öğrenme Ölçeği'dir. Mesleklerarası Öğrenme, Yetkinlik ve Özerklik, Gerçek İşbirliği Algısı, Öğrenmeye Hazır Olma ve Mesleki Kimlik son test puanlarında artışlar ve anlamlı farklılıklar bulduk (p<0.05). Bulgularımız, SOYAÇ Modeli'nin öğrencilerin diğer mesleklerle etkileşime girme ve işbirliği yapma algıları üzerinde önemli ve faydalı bir etkisi olduğunu doğrulamaktadır.
Sağlık ve sosyal bakım öğrencilerine mesleklerarası öğrenme deneyimleri sağlamak: İstanbul’dan SOYAÇ modeli
Keywords: Education; Health; Students; Eğitim; Sağlık; Öğrenciler